«Відомості про відступників» як історичне джерело конфесійних конверсій у 30-ті роки ХІХ ст. (на прикладі Волинської губернії) - Holiy, Roman; Голій, Роман (Східноєвропейський національний університет ім. Лесі Українки, 2013)
У статті проаналізовано інформаційний потенціал документування конфесійних трансформацій у Волин-ській губернії. Зокрема розглянуто випадки переходу з православ’я до греко-католицтва та католицтва в умовах антикатолицької політики в Російській імперії у 30-х роках ХІХ ст.In the article analyzed the information potential of documenting the religious transformations in the Volyn province is. In particular, we consider the cases of transition from Orthodoxy to the Greec-Catholicism and Catholicism in the conditions of anti-Catholic policy in the Russian Empire in 30-ies of 19th century. It was found out that in the Volyn province the ponderable centers of conversion of the Orthodox parishioners were catholic and greco-catholic parishes, where monks served. By grounds for including of person to the list «of apostates» were: information about Orthodox of christening person; records in church books on an acceptance by the face of mysteries in the Orthodox temple; information about former belonging of person to Orthodoxy.
«The Lists About Apostates» as a Historical Source of Confessional Conversions in 30th Years of XIX Century (on the Example of the Volyn Province)
Keywords: православ’я; греко-католицтво; римо-католицтво; Волинська губернія; державна політика; Orthodox; the Greec-Catholicism; Rome-Catholicism; the Volyn province; public politics